Evaluation of co-designed online teacher training program for providing neuroscience- informed mental health intervention to Japanese children - Takizawa, Yu; Bambling, Matthew; Teoh, Hsien-Jin; Edirippulige, Sisira (Frontiers in Education, 2024)
While mental health problems are prevalent among children, Japanese schools face challenges in providing effective mental health support to children partly due to a lack of training in mental health intervention. This study aimed to address this problem by evaluating a co-designed online teacher training program to provide a neuroscience-informed mental health intervention (NIMHI) to Japanese children.The present study evaluated the effectiveness of an online teacher training program by conducting a single-arm trial involving a group of 20 teachers and 245 children aged 8-12 from a regional Japanese primary school. The researcher delivered online training to Japanese teachers, who subsequently administered NIMHI to Japanese children over a four-week period. The evaluation involved the administration of pre-and post-intervention student questionnaires, pre-and posttraining teacher questionnaires, and post-intervention teacher interviews.Results: After the delivery of the training program, 80% of Japanese teachers expressed strong or moderate satisfaction with the training. There were significant improvements in teachers' knowledge, perceived skills, self-efficacy, and acceptability of using NIMHI. Teachers implemented intervention strategies at least twice a week over four weeks. Following the intervention, 70% of teachers reported qualitative changes in students' mental health, such as more stable emotions. However, there were no significant changes in students' emotional problems, school enjoyment, and psychological wellbeing.The findings offer a fresh perspective on the effectiveness of utilising digital technology, as a modality for delivering training to Japanese teachers. However, the absence of quantitative changes in students' mental health could suggest that the effectiveness of the online teacher-training program may not have been sufficiently robust. Further improvements in the online teacher-training program would be useful, such as providing tablet applications to assist teachers in implementing suitable intervention strategies and teaching a more focused range of strategies.